Challenges and possible solutions for english teaching and learning in the province of Guanacaste, Costa Rica - Castro Arias, Katherine (2022)
This essay explores and presents challenges and possible solutions associated with English teaching and learning in Guanacaste, Costa Rica. It covers the reality of public bilingual education in Guanacaste, single-teacher schools, and the rural university context. The proposed solutions are contextualizing the educational ambiance, communication between the school and the parents, alliances between the public and private sectors, strategies to handle negative emotional factors and to promote motivation among students.